(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Field trials were conducted during the 2017 wet season at the Dryland Teaching and Research Farm of , Usmanu Danfodiyo University Sokoto (Latitude 13o 7’N, Longitude 50 10’E’) and Dutsinma in Katsina State (longitude 70 29’E, Latitude 12o 27’N ). The aim was to evaluate Pendimethalin, Butachlor and S-Metolachlor for weed control in soya beans. Treatments consisted of Pendimethalin at 0.8, 1.0 and 1.2 kg a.i./ha, Butachlor at 1.5, 1.8 and 2.0 kg a.i./ha and S-Metolachlor at 0.6, 1.3 and 1.9 kg a.i./ha and control where weeding was done manually at 4 and 6 weeks after sowing. The experiment was laid out in a Randomized Complete Block Design and replicated three times. Data were collected on weed parameters. Results obtained indicated that all the herbicide treatments significantly reduced weed infestation during the first four weeks after sowing but the crop experienced competition with weeds thereafter which varied according to the types of herbicides and their rates. Pendimethalin (1.0 and 1.2 kg a.i./ha, S-Metholachlor (1.9 kg a.i./ha) and Butachlor (2.0 kg a.i./ha) exhibited superior performance over other herbicide treatments. However, Pendimethalin at 1.2 kg a.i./ha caused injury to the plants though not prolonged. Hoe weeded plots faced early competition with weeds but were relatively weed-free during the reproductive phase of the crop. Soya bean farmers in Katsina and Sokoto could apply Butachlor 2.0 kg a.i./ha or S-Metolachlor 1.9 kg a.i./ha or Pendimethalin 1.0 kg a.i./ha for good control of weeds during the establishment phase of soya bean.